2009
DOI: 10.1016/j.jcps.2009.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Self‐regulation of consumer decision making and behavior: The role of implementation intentions

Abstract: People may use the self-regulatory strategy of forming implementation intentions (i.e., if-then plans) to make better consumer decisions and facilitate the translation of those decisions into action. First, research on the mechanisms and effects of implementation intentions is reviewed. Second, we discuss how implementation intentions can be used to improve consumer decision making by promoting attention control and information elaboration, and overcoming disruptive influences. Third, we consider the various p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 103 publications
4
81
0
Order By: Relevance
“…Electronically published January 26, 2012 Fishbein and Ajzen 1975) and the strategies that facilitate goal success (Gollwitzer and Sheeran 2009;Myrseth and Fishbach 2009). One program of research shows that people are more likely to follow through with a goal if they form implementation intentions: plans that specify the procedures by which a goal will be attained and the circumstances under which specific behaviors will be enacted (Gollwitzer 1999).…”
Section: Baba Shiv and Ann Mcgill Served As Editors And Pierre Chandomentioning
confidence: 99%
See 1 more Smart Citation
“…Electronically published January 26, 2012 Fishbein and Ajzen 1975) and the strategies that facilitate goal success (Gollwitzer and Sheeran 2009;Myrseth and Fishbach 2009). One program of research shows that people are more likely to follow through with a goal if they form implementation intentions: plans that specify the procedures by which a goal will be attained and the circumstances under which specific behaviors will be enacted (Gollwitzer 1999).…”
Section: Baba Shiv and Ann Mcgill Served As Editors And Pierre Chandomentioning
confidence: 99%
“…To elaborate, several prominent models of goal pursuit posit that a strong commitment to a goal leads to planning (Gollwitzer 1990;Locke and Latham 1990;Orbell and Sheeran 2000). On the basis of those models, empirical studies measure commitment to show that prior commitment moderates planning effects and/or that planning does not strengthen commitment (Gollwitzer and Sheeran 2006;Parks-Stamm and Gollwitzer 2009). In comparison, our argument suggests that an ironic effect of implemental planning is its potential to undermine the very commitment that prompts people to plan in the first place.…”
Section: Planning and Commitment Within A Goal Systemmentioning
confidence: 99%
“…They showed that implementation intentions facilitate regulation of future inner disruptive states, such as longing, obtrusive thoughts, feelings, and physiological states. Moreover, in their review article Gollwitzer and Sheeran [29] show that implementation intentions facilitate self-regulation in the context of consumer decision-making. They, for instance, report that implementation intentions improve consumer decisions by promoting control of attention and by overcoming various disruptive influences and factors on decisions (such as emotions, ego depletion, etc.).…”
Section: Implementation Intentionsmentioning
confidence: 99%
“…However, the effects of implementation intentions in the context of TPB can be weakened by other constructs. Gollwitzer and Sheeran (2009) outlined that "when one doubts the appropriateness of forming implementation intentions, no implementation intention effects can be expected" (Gollwitzer&Sheeran, 2009, p. 603). This may also be the case when strong habits are given -the automaticity associated with them may override the automatic effect of implementation intentions (Verplanken&Faes, 1999).…”
Section: Hypotheses Developmentmentioning
confidence: 99%